Effects of nano-hydroxyapatite paste on enamel microporosity after bleaching treatment - Nikmatus Sa'adah; Gadis Meinar Sari; Elyana Asnar (Faculty of Dentistry, Universitas Gadjah Mada, 2018)
Bleaching or teeth whitening is a popular dental conservative treatment to enhance aesthetics. Bleaching treatment in many cases has successfully improved aesthetics but still remains the side effects. It can cause some changes in enamel structure leading to demineralization characterized by the emergence of microporosity on the enamel surface. Nano-hydroxyapatite is potential to re-mineralize earlyenamel lesions. This study aims to identify the effect of nano-hydroxyapatite on enamel microporosity after bleaching treatment. Twelve rabbits were randomly divided into two groups. The control and treatment group administered a placebo and nano-hydroxyapatite paste respectively, for 7 days after bleaching treatment. Once the treatment was completed, the rabbit was sacrificed, the jaw was decapitated, upper and lower incisors of the rabbit were separated from the jaw. Subsequently, the sample preparation wasconducted for examination of enamel microporosity depth by using scanning electron microscope. The results showed the control group had more microporositycompared to the treatment group. The independent t-test result showed that enamel microporosityhad a significant value of 0.003 (p <0.05) meaning that enamel microporosity between both groups had a significant difference. The conclusion of this study was administration of nan-hydroxyapatite paste reduced enamel microporosityin the administration of nano-hydroxyapatite pastes compared to the placebo pastes after bleaching treatment.